Intercultural Reflection Journals as a Pedagogical Tool: Enhancing Cultural Awareness in Academic Speaking Classes - Anugerah Febrian Syam (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study examines how intercultural reflection journals can support the development of students’ intercultural awareness in academic speaking classes. Methodology: Using an Ethnographic Classroom Study design, the research involved 18 EFL students at a private university. Data were gathered from intercultural reflection journals, classroom observations, audio recordings, and semi-structured interviews, then examined through thematic analysis using coding, categorisation, and theme development. Main Findings: The findings show that intercultural awareness develops gradually, moving from surface awareness toward deeper reflection. This process is shaped by classroom interaction and moments of tension, including discomfort and ambiguity. Novelty/Originality of this study: The development is neither linear nor uniform across students. The study suggests that intercultural reflection journals are most effective when embedded in pedagogical practices that encourage dialogue, critical reflection, and meaning negotiation.